Cctv customer location data processing on webgis based a & s security system - Zefri Zulmi (Trigin Publisher, 2023)
Geographic Information System (GIS) is a computer-based information system, designed to work with data that has spatial information (spatial reference). Currently the information data about the location of CCTV Customers on the A & S Security System in Medan City has not been inventoried in a spatial-based web information system, the mapping data for CCTV Customer locations on the A & S Security System in Medan City still uses Microsoft Word and not programmed. For this reason, the authors created a solution with a Geographic Information System, which is an information system that is used to enter, process, and produce geographically or geospatially referenced data, to support decision making in planning. This information system will later have a visualization in the form of a web that is used to map the location of CCTV Customers on the A & S Security System in Medan City. In the development of the CCTV customer location processing system at the A & S Security System in Medan City, PHP and MySql programming languages ​​were used as database systems.